ANALISIS SKALA EKONOMIS PADA INDUSTRI KAIN SONGKET DI DESA SIDEMEN KABUPATEN KARANGASEM - Karsani, Kadek Ayu; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No.4, April 2018 (pp. 617-867), 2018)
The growth of industrial sector of songket songwriter in Sidemen Village of Karangasem Regency is greatly influenced by economical scale and efficiency of a com pany that enter in the industry. This study wanted to find out the influence of labor and capital, either simultaneously or partially to the songket cloth industry in Sidemen Village , analyzed the economic scale of the songket cloth industry in Sidemen Village , analyzing the efficiency of songket cloth industry in Sidemen Village , analyzing the production properties of the songket cloth industry in Sidemen Village . The result of analysis prove labor and capital have significant influence simultaneously on songket cloth industry in Sidemen Village with R2 value that is equal to 0,237 which means that statistically 23,7% from economical scale variation on industrial production of songket cloth in. Sidemen Village explained by power work and venture capital . The economic scale of the songket cloth industry in Sidemen Village is in a condition of increasing return of scale . The production of songket cloth industry in Sidemen Village is labor intensive.